2021
DOI: 10.3390/healthcare9080923
|View full text |Cite
|
Sign up to set email alerts
|

Are Strength Indicators and Skin Temperature Affected by the Type of Warm-Up in Paralympic Powerlifting Athletes?

Abstract: (1) Background: the present study aimed to evaluate the effect of different types of warm-ups on the strength and skin temperature of Paralympic powerlifting athletes. (2) Methods: the participants were 15 male Paralympic powerlifting athletes. The effects of three different types of warm-up (without warm-up (WW), traditional warm-up (TW), or stretching warm-up (SW)) were analyzed on static and dynamic strength tests as well as in the skin temperature, which was monitored by thermal imaging. (3) Results: no di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…If the participant could not perform a single repetition, 2.4% to 2.5% was subtracted from the load used in the test. The subjects rested for 3 to 5 min between attempts [25,26].…”
Section: Procedures 241 Load Determinationmentioning
confidence: 99%
“…If the participant could not perform a single repetition, 2.4% to 2.5% was subtracted from the load used in the test. The subjects rested for 3 to 5 min between attempts [25,26].…”
Section: Procedures 241 Load Determinationmentioning
confidence: 99%
“…Seven studies [ 19 , 20 , 21 , 22 , 23 , 24 , 25 ] were excluded with reason ( n = 2, not reporting sufficient details; n = 5, not disaggregating data according to para-sports discipline). Finally, 37 studies [ 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 ] were retained in the present scoping review. We found that the included studies focused on a range of aspects involving health, classification, the etiology of injuries, and performance.…”
Section: Resultsmentioning
confidence: 99%
“…Two randomized, cross-over studies [ 26 , 27 ] in a sample of 12 elite Brazilian male PP athletes (aged 24.14 ± 6.21 years, body weight 81.67 ± 17.36 kg, experience 4.45 ± 0.31 years) [ 26 ] and in a sample of 15 elite Brazilian male PP athletes (aged 28.47 ± 5.79 years, body weight 81.75 ± 17.33 kg, experience 2.43 ± 1.03 years) [ 27 ] investigated the impact of three different warm-up conditions (no warm-up, traditional warm-up consisting of dynamic resistance exercises, and stretching warm-up) on a set of PP performance-related outcomes and variables. These included dynamic (1-RM and mean propulsive velocity) and isometric strength (rate of force development, maximum isometric force, time to maximum isometric force, fatigue index, impulse, variability, peak torque) and skin temperature.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Weight increments were added until the maximum load that could be lifted once was reached. If the exerciser could not perform a single repetition, 2.4 to 2.5% of the load used in the test was subtracted [ 21 , 22 ]. The subjects rested for 3–5 min between attempts.…”
Section: Methodsmentioning
confidence: 99%